Edukasi Model Pendampingan Orang Tua dalam Upaya Meningkatkan Pemahaman Terhadap Pendidikan Inklusi Berbasis Kolaborasi SDN 4 Palangka Raya - Yuherlita Marneci; Yuel Yuel; Lisa Maneli; Yoan Colina; Sapta Lelunu; Susilawati Susilawati; Debi Silvia Dinata (Institut Kristen Teologi Real Batam, 2026)
This community service activity aims to increase the understanding and active involvement of parents in supporting inclusive education at SDN 4 Palangka Raya. This activity uses the Participatory Action Research (PAR) approach through the following stages: knowing, understanding, planning, acting, reflecting, and evaluating. The activity involves teachers, parents, and accompanying teachers through collaborative educational forums and intensive mentoring. The results of the implementation of this service activity stated that before the implementation and implementation of the collaboration-based parent mentoring model, the aspect of parental understanding and involvement in inclusive education was only 32%. However, after implementation and mentoring, the aspect of understanding and involvement of parents in inclusive education became 80%. This means that there was an increase of 48 percentage points. Thus, this service program succeeded in increasing the level of understanding and active involvement of parents in inclusion education at SDN 4 Palangka Raya. This program also produces a mentoring model that can be replicated as a strategy to strengthen the school community in realizing an inclusive learning environment. Through this community service activity, it makes a real contribution to strengthening inclusive education practices in elementary schools through a collaborative and participatory approach. Keywords: children with special needs; collaborative mentoring model; inclusive education; parental involvement; participatory action research Abstrak Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan pemahaman dan keterlibatan aktif orang tua dalam mendukung pendidikan inklusi di SDN 4 Palangka Raya. Kegiatan ini menggunakan pendekatan Participatory Action Research (PAR) melalui tahapan: knowing, understanding, planning, acting, reflecting, dan evaluating. Kegiatan melibatkan guru, orang tua, dan guru pendamping melalui forum edukasi kolaboratif serta pendampingan intensif. Hasil pelaksanaan kegiatan pengabdian ini menyatakan bahwa sebelum pelaksanaan dan implementasi model pendampingan orang tua berbasis kolaborasi, aspek pemahaman dan keterlibatan orang tua dalam pendidikan inklusi hanya 32%. Namun setelah pelaksanaan dan pendampingan, aspek pemahaman dan keterlibitan orang tua dalam pendidikan inklusi menjadi 80%. Artinya terjadi peningkatan sebesar 48 poin persentase. Dengan demikian, program pengabdian ini berhasil meningkatkan tingkat pemahaman dan keterlibatan aktif orang tua dalam pendidikan inklusi di SDN 4 Palangka Raya. Program ini juga menghasilkan model pendampingan yang dapat direplikasi sebagai strategi penguatan komunitas sekolah dalam mewujudkan lingkungan belajar yang inklusif. Melalui kegiatan pengabdian masyarakat ini memberikan kontribusi nyata bagi penguatan praktik pendidikan inklusi di sekolah dasar melalui pendekatan kolaboratif dan partisipatif. Kata kunci: anak berkebutuhan khusus; kolaborasi sekolah-keluarga; model pendampingan; participatory action research; pendidikan inklusi